2013
DOI: 10.12659/ajcr.883867
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic giant solitary fibrous tumor

Abstract: BackgroundSolitary fibrous tumor of the pleura is a rare, usually benign, and slow-growing neoplasm. Complete surgical resection for giant tumor of the pleura is challenging because of poor exposure and a large blood supply. We report the case of a giant hypervascular fibrous tumor that filled nearly the entire left hemithorax and anterior mediastinum, and its preoperative management.Case Report:A 59-year-old woman presented to us with exertional dyspnea and chest pain. A chest radiograph showed the right hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Giant SFTP is a rare form of pleural disease that is only occasionally cited in the literature, usually in single cases . Larger tumors, more than 10 cm or 15 cm in diameter, occupying a larger space, and compressing other thoracic structures, may cause symptoms such as dyspnea, chest pain, cough, and fatigue .…”
Section: Discussionmentioning
confidence: 99%
“…Giant SFTP is a rare form of pleural disease that is only occasionally cited in the literature, usually in single cases . Larger tumors, more than 10 cm or 15 cm in diameter, occupying a larger space, and compressing other thoracic structures, may cause symptoms such as dyspnea, chest pain, cough, and fatigue .…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] There are many cases reported in the literature showing that the surgeons were unable to complete tumor resection operations due to massive bleeding. [10,14,15] Neuroendocrine tumors are highly vascular in nature, and many patients experience intraoperative hemorrhagic complications. [16] Morandi et al [14] reported that, during right thoracotomy, the mass which was reported as a hemangiopericytoma was highly vascularized and massive bleeding from the tumor tissue occurred during the dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Aydemir et al [15] reported a patient with a giant (15 cm) solitary fibrous tumor supplied by multiple intercostal arteries and an aberrant artery branched off the celiac trunk in his subdiaphragmatic region in whom embolization failed due to a high number of arteries. The authors decided to control possible bleeding by inducing total circulatory arrest through cardiopulmonary bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical excision of giant intra-thoracic SFTs is considered a surgical challenge due to poor exposure, significant tumor blood supply, and heavy adhesions, among other characteristics. [9,12] Aydemir et al [12] from Turkey reported a 59-year-old female with a giant intrathoracic SFT that almost completely filled the right hemithorax for whom the operation was terminated after taking a biopsy because of excessive bleeding during dissection. Later on, angiography showed that the tumor was supplied by multiple intercostal arteries as well as an aberrant branch from the celiac trunk.…”
Section: Discussionmentioning
confidence: 99%
“…We think that excessive bleeding from the raw chest wall in our patient could be due to a similar blood supply via intercostal arteries and we agree with the authors that CPB and total circulatory arrest are not valid alternatives to control the bleeding. We share the advice of many authors [9,[12][13][14] to perform a preoperative CT angiography for such huge tumors to reveal the feeding arteries and perform preoperative embolization to reduce the intraoperative blood loss. In addition, we recommend auto-transfusion as a good intraoperative measure to save the patients' lives.…”
Section: Discussionmentioning
confidence: 99%